Utilisation Of Voice Recordings as Electronic Evidence in Corruption Cases - Furcony Putri Syakura (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Electronic evidence is essential for exposing corruption. Voice recordings and electronic trial evidence are difficult to validate, despite their importance. Thus, standardisation is needed to use this evidence to aid the judicial process, notably law enforcement, for corruption. Under this theory, the author first discusses how to validate voice recordings as electronic evidence in corruption prosecutions—a assessment of their validity and believability. Second, analyse what barriers would arise when using electronic device voice records as corruption case evidence. Researchers use normative legal research with a statutory methodology. The Main Statutory will be using Law No. 19/2016 on Information and Transactional Electronic and Law No. 8/1981 on “Kitab Undang-Undang Hukum Acara Pidana”. Data is collected using library research. This study found that clear norms are essential to ensure judicial justice. Electronic evidence, including voice recordings, must be validated for legal integrity and corruption prosecutions.